When Media Owning Sports Club: Republika Editorial Policy in News Coverage about Inter Milan and Satria Muda - Fadlan A. Ramadan; Narayana M. Prastya (Department of Communications, Universitas Islam Indonesia, 2019)
This paper aims to know about content of the news and editorial policy in Republika, when the media coverage news about Inter Milan and Satria Muda Pertamina. Both of the sport teams are owned by Erick Thohir, the boss of Republika. Based on literature, the interest of mass media owner and newsroom policy often difference. Because mass media owner have their goals, meanwhile the newsroom should obey the professional journalism standard. At the practice, the newsroom make usually make a compromise.This paper uses qualitative research methods. The data collecting technique are using documentary research and interviews. The documentary research held by collecting and analyzing news about Inter Milan and Satria Muda in Republika daily newspaper (print edition). The time period for Inter Milan news is August 2014 to October 2015 while Satria Muda in January to June 2016. At the time frame, both club did not win any competition that they were participated. So, at that time the club was in the negative period. The interviews held with the representative of the Republika sport section editor to confirm the result from text analysis.As the findings from text analysis, Republika always brings good news to Inter Milan and Satria Muda Pertamina, although both team was not winning the competition, and there were relatively much negative results in the single season. Republika explained that they have direct access to news sources from Inter Milan and Satria Muda Pertamina directly. So Republika will gain more information from both club than the other media. Not only in sporting theme (e.g. match results, preview, review), Republika sometimes deliver the news about the figure of Erick Thohir. Keywords : editorial policy, media ownership, sport journalism, sport communication